(untitled) (Research, Society and Development, 2022)
The objective of this study was to demonstrate the occurrence of parasite larvae in places where there are more children. The soil samples were collected and taken to the laboratory of the Universidade Estadual da Paraíba and there the technique of Hoffman, Pons and Janer or Lutz was approached, or the spontaneous sedimentation method that basically consists of mixing the collected soil with water, filtering it by a surgical gauze and keeping it at rest, which forms a sedimentation at the bottom of the calyx. Two of the places where the samples were collected (public squares and streets of eight districts and twelve different points in the city of João Pessoa and in the metropolitan region) the prevalence of the parasite Strongyloides stercoralis was observed. Of the 48 samples duly prepared in the laboratory, 42.85% of the result was obtained in Praça São Gonçalo. The parasite Strongyloides stercoralis can cause diseases to society, being strongyloidiasis that is usually asymptomatic. People with low immunity affected more severely, causing hyperinfection. Given these problems, it is of great importance to care for society, carrying out soil analysis in public places, so that the self-level of infection by this parasite can be prevented. In view of the facts mentioned above, such prevalence may be related to the number of dogs and cats in the environment and it is worth mentioning that there is a need for intervention by authorities in order to alleviate the situation.